The Effect of water level and cow manure fertilizer application method on rice yield and Cyperus rotundus weed - Supriyono Supriyono; Setyaningrum Desy; Pardono; Ari Nurrohmah Maulina (BIO Web of Conferences)
Climate change is a global issue that affects rice production. Rice production in Indonesia experiences fluctuations due to several factors, such as water availability, nutrients, and weeds. The study aims to examine the effect of high water levels and organic fertilizer application methods on rice growth and yield and the growth of Cyperus rotundus weeds. The research used a completely randomized design of two factors arranged factorially and three replications. The first factor was the high water level with three levels, namely 0-1, 1-2, and 2-3cm. The second factor was applying organic fertilizer with three levels: immersing it 5 cm, spreading it on the surface of the ground, and mixing it evenly with the soil. The combination of water level and organic fertilizer application method affects the number of productive rice tillers. The lower the water level (0-1 cm), the higher the amount of organic fertilizer mixed with soil, which shows the highest number of rice tillers. he higher the water level, the higher the plant, but the weight of dry rice grains decreases. Applying manure mixed with soil can increase the number of productive panicles per plant and reduce rice grains’ dry weight but reduce Cyperus rotundus weeds’ growth.